2017
DOI: 10.4025/actascibiolsci.v39i1.33860
|View full text |Cite
|
Sign up to set email alerts
|

<b>Use of human cadavers in teaching of human anatomy in brazilian medical faculties

Abstract: ABSTRACT. The Human Anatomy is the study of human body structure and it has been related to the use of cadavers through the history. The aim of this research was to investigate the use of human cadavers in practical classes of human anatomy in Brazilian medical schools, and it was also made the identification of alternative methodologies and new technologies applied to the teaching of Anatomy. The research was conducted at the Faculdade Integral Diferencial from January to December of 2015. The population stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…In a recent study, [18] researchers stated that in order to maintain donation programs, it is essential first to understand the meaning of public opinion and then adopt strategies to improve donations. In addition, the same author suggested that donor profile surveys provide useful information about donors and the reasons they donate, which can be used to direct potential donors when setting donor programs, to circumvent difficulties in finding donors, or to monitor changes in donor profiles [18,19]. Body donation research shows that the identification of donor profiles facilitated campaigns aimed at informing the target population about voluntary donation of cadavers [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, [18] researchers stated that in order to maintain donation programs, it is essential first to understand the meaning of public opinion and then adopt strategies to improve donations. In addition, the same author suggested that donor profile surveys provide useful information about donors and the reasons they donate, which can be used to direct potential donors when setting donor programs, to circumvent difficulties in finding donors, or to monitor changes in donor profiles [18,19]. Body donation research shows that the identification of donor profiles facilitated campaigns aimed at informing the target population about voluntary donation of cadavers [19].…”
Section: Discussionmentioning
confidence: 99%
“…Being a practically oriented subject, the challenges for anatomy education due to the outbreak of Covid‐19 are significant (Gupta and Pandey, 2020; Singal et al, 2020). One unique aspect of anatomy education that is being affected by the Covid‐19 pandemic is the use of cadavers in teaching and learning (Chakraborty et al, 2010; Lopes et al, 2017). This teaching method has remained useful from historical times to the present (Ghosh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Esta consiste na exploração das estruturas anatômicas de forma sistemática que ajuda a expor topograficamente os órgãos e tecidos para o ensino visual destes (NOBESCHI L, et al, 2018). O estudo anatômico é uma das mais antigas ciências médicas que constituem o cotidiano do estudante de medicina (LOPES ISL, et al, 2017). Este é de extrema importância devido a oportunidade que disponibiliza ao discente a desenvolver as habilidades e competências exigidas na atuação profissional cotidiana com mais segurança e pratica medica, por meio da dissecação.…”
Section: Introductionunclassified
“…Porem este treinamento em peças anatômicas disponíveis para o ensino está se tornando uma pratica incomum (MEDEIROS ARC, et al, 2013;ÖZCAN S, et al, 2015) O surgimento das novas tecnologias digitais ampliou o ensino da anatomia, possibilitando a substituição da dissecação por recursos de projeções audiovisuais e utilização de softwares (NOBESCHI L, et al, 2018;LOPES ISL, et al, 2017). Entretanto, o ensino baseado em cadáveres é reconhecido pelos alunos, docentes e clínicos como o melhor método para aprender anatomia, pois este inclui detalhes e variações anatômicas que são essenciais para a formação acadêmica de discentes da área da saúde, especialmente estudantes de medicina (LOPES ISL, et al, 2017;PATEL, K, et al, 2008;SHEIKH AH, et al, 2016). Ademais, muitos dos recursos tecnológicos de aprendizagem anteriormente citados, muitas vezes não poderão ser disponibilizados em muitas escolas de países em desenvolvimento, devido limitações financeiras (NOBESCHI L, et al, 2018).…”
Section: Introductionunclassified